The Effects of Non-Recourse Mortgages on Default Risks and Households' Surplus - Keeyoung Rhee (KDI Journal of Economic Policy, 2018)
We study whether a default option attached to non-recourse mortgages improves borrowers' surplus from mortgage financing. By defaulting on mortgage debt, borrowers can save their non-collateralized income from being foreclosed. In exchange, borrowers must forgo non-monetary surplus from retaining any collateral. Banks may charge a high mortgage rate due to increased default rates. We find that the interest rate of non-recourse mortgage decreases with the borrower's surplus from home ownership. Moreover, non-recourse mortgages benefit only borrowers who deem housing property as an investment asset. Hence, the transition to a non-recourse mortgage is detrimental to welfare if the borrower enjoys a large surplus from home ownership. Although the borrower privately knows how much surplus she enjoys from home ownership, a menu of non-recourse mortgage contracts may exist, yielding a separating equilibrium without information rent.
Keywords: D82; G18; G21; 330; Non-recourse Mortgage; Strategic Default; Adverse Selection